Secret language of the soul - "Hope, Jane" (San Franscisco, 1997)
The latest in the Secret Language series, The Secret Language of the Soul is an inspiring survey of faith and ritual through the ages, from Native American vision quests to chakras, avatars, and archangels. Turning to all the major religious traditions as well as more obscure philosophies, author Jane Hope considers destiny, enlightenment, and salvation; the lives of spiritual figures; and esoteric ideas as diverse as Tantric meditation and spirit helpers. Original and ancient artworks depict some of the most profound and compelling images ever devised -- the Tibetan Wheel of Life; the Judaic seven-branched candlestick; the ancient Egyptian Eye of Horus. In the tradition of Huston Smith's World Religions, this richly illustrated volume is an inviting universal guide to the realm of the divine.
Keywords: Religion